Strengthening Students’ Discipline Through Religious Programs at MAN 1 Jombang - Putra, M. Aditya Tri; Laily Masruroh (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
Disciplinary character remains underexplored in existing studies on religious programs, which have predominantly focused on religious character formation and worship motivation. This study analyzes the implementation of religious programs in enhancing students' disciplinary character at Madrasah Aliyah Negeri 1 Jombang using a qualitative case study design. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman's interactive model. The findings reveal that nine structured religious programs including morning habituation, congregational prayers, BTQ (reading and writting Quran), takhassus, istighosah, Ramadan study, PHBI, Remas, and tahfidz cultivate disciplinary character through internalization processes ranging from behavioral compliance to intrinsic motivation, reflected in improved punctuality, worship consistency, regulatory adherence, and self-responsibility. Supporting factors include collective institutional commitment and active teacher modelling, while inhibiting factors include students' psychological reactance and insufficient family support. This study contributes a multi-layered analytical framework demonstrating that discipline is cultivated through social accountability, identity formation, and spiritual motivation within a faith-based educational context.